Hypofractionated radiotherapy regimens after organ-sparing surgery for stages I-IIa breast cancer - Yu. V. Efimkina; I. A. Gladilina; M. I. Nechushkin; O. V. Kozlov (ABV-press, 2014)
The results of basic clinical randomized trials of hypofractionated (HF) radiotherapy (R T) regimens used after organ-sparing su rgery for Stages I-IIa breast cancer (BC) were analyzed. The HF adjuvant RT regimens were shown to be safe and an alternative to the standard RT in patients with BC after organ-saving operations.